PENGARUH KEPERCAYAAN MEREK DAN KEBIASAAN MENGGUNAKAN PRODUK TERHADAP LOYALITAS PELANGGAN DI MCDONALD’S SAMARINDA - Nurwahida Nurwahida; Noor Ellyawati; Ratna Fitri Astuti (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
The purpose of the research was to determine the effect of brand trust and habitual behavior on McDonald's Samarinda customer loyalty. This type of research uses descriptive methods with a quantitative approach. The sample used was 100 McDonald's Samarinda customers. The data analysis used is a multiple linear regression analysis. The results of the study show that brand trust and habitual behavior simultaneously have a significant effect on customer loyalty. In the coefficient of determination (R2) test, it is known that the magnitude of the effect of brand trust and habitual behavior is 55.9%, while the remaining 44.1% is influenced by variables outside of brand trust and habitual behavior, such as customer satisfaction. The conclusion of the study is that McDonald's Samarinda customers repurchase products 3–4 times a month and recommend the McDonald's brand to the surrounding environment or other people because they have brand trust and habitual behavior.Keywords: Brand Trust; Customer Loyalty; Habitual Behaviour